Coastal gradients of small microplastics and associated pollutants influenced by estuarine sources. (January 2022) - González-Ortegón, Enrique; Sendra, Marta; Sparaventi, Erica; F. Sánchez Leal, Ricardo; de los Ríos, Isaac; Baldó, Francisco; González-Fernández, Daniel; Yeste, María Pilar
Abstract: Small microplastics (SMPs) in the gulf of Cadiz was sampled at 5 m depth by pumping it through the ship's pipe system and filtered through a 45 μm mesh size net. Our study reveals that higher densities have been found (130 mg·m −3 ) compared to other regions worldwide and these densities decreased from the coastline to the outer stations, showing a general coastal gradient influenced by estuarine outflows. SMPs with a size range between 45 and 193 μm were predominant and most of them composed by polyethylene and polypropylene. The metals associated with the MPs were mainly Na (21.1%), K (11.3%), Fe (8.5%), Ca (2.1%), Cr (1.8%), Zr (13.3%) and Hf (0.7%). The high proportion of Zr compared to Fe, which is different from what can be found in the environment, suggests that this metal is intrinsic to the materials used in catalytic processes during plastic production. Highlights: Subsurface waters contain high small microplastics (SMPs) abundances SMPs clear pattern in relation to the distance from the coast SMPs composed mainly by polyethylene and polypropylene Metals associated with the MPs intrinsic to plastic production